2021
DOI: 10.1021/acs.jafc.1c02801
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Lectin Protein Allergen of Kidney Beans (Phaseolus vulgaris L.) and Desensitization Food Processing Technology

Abstract: With the increase of food allergy events related to not properly cooked kidney beans (Phaseolus vulgaris L.), more and more researchers are paying attention to the sensitization potential of lectin, one of the major storage and defensive proteins with the specific carbohydrate-binding activity. The immunoglobulin E (IgE), non-IgE, and mixed allergic reactions induced by the lectins were inducted in the current paper, and the detection methods of kidney bean lectin, including the purification strategies, hemagg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 205 publications
(378 reference statements)
0
5
0
Order By: Relevance
“…Upon ingestion, legume lectins bind to particular receptor sites on the intestinal epithelial cell surface, interfering with nutrient absorption across the intestinal wall in a non-specific manner [ 131 , 141 ]. Once bound to the digestive tract, the lectin may alter part or all of the digestive, absorptive, protecting, and secretory functions of the entire digestive system, as well as cellular proliferation and turnover.…”
Section: Naturally Occurring Plant Food Toxicantsmentioning
confidence: 99%
“…Upon ingestion, legume lectins bind to particular receptor sites on the intestinal epithelial cell surface, interfering with nutrient absorption across the intestinal wall in a non-specific manner [ 131 , 141 ]. Once bound to the digestive tract, the lectin may alter part or all of the digestive, absorptive, protecting, and secretory functions of the entire digestive system, as well as cellular proliferation and turnover.…”
Section: Naturally Occurring Plant Food Toxicantsmentioning
confidence: 99%
“…With the increase in food allergy events related to kidney beans, more and more researchers are paying attention to the allergenic potential of lectins in kidney beans. 51 Lectin is a nonenzymatic sugar-binding protein that can bind to specific monosaccharides and oligosaccharides to form complexes. 52 In addition, sensitization of kidney bean lectin proteins has also been reported in mice, pigs, cattle, etc., 53,54 whereas studies found that deglycation modification contributed to the reduction of soybean lectin allergen sensitivity, which also indicated the role of carbohydrates for lectin sensitization.…”
Section: Effect Of Food Matrix Interactions On Food Allergiesmentioning
confidence: 99%
“…After covalent binding, allergenic epitopes can be modified or combined to lose allergenicity, and glycoproteins in animals and plants can be deglycated, which can lead to the destruction of allergenic epitopes (Figure C). With the increase in food allergy events related to kidney beans, more and more researchers are paying attention to the allergenic potential of lectins in kidney beans . Lectin is a nonenzymatic sugar-binding protein that can bind to specific monosaccharides and oligosaccharides to form complexes .…”
Section: Effect Of Food Matrix Interactions On Food Allergiesmentioning
confidence: 99%
“…Legumin is a hexameric protein with a stiff conformation and considerable quaternary structure, with a molecular mass of 300 to 400 kDa [ 9 , 51 ]. It is composed of six subunit pairs (each around 60 kDa), which interact noncovalently, and is further assembled through two trimeric intermediates ( Figure 2 A).…”
Section: Composition and Structure Of Pulse Protein Isolatesmentioning
confidence: 99%